Parametric study of Cylindrical Dielectric Resonator Antenna (CDRA) feeder with symmetric parabolic reflector - Ali, S.M. (Maxwell Science Publications, 2015)
In this study a parabolic reflector antenna is designed and fabricated for IEEE 802.11a WLAN application. Initially, a single element circular tuning slot coupled Cylindrical Dielectric Resonator Antenna (CDRA) feeder is designed and fabricated for a symmetric parabolic reflector. Subsequently, the designed feeder is integrated at the focal point of the parabolic reflector to provide unidirectional radiation pattern with improved gain and sidelobe levels. The measured fractional impedance bandwidth achieved for the proposed antenna is 1.8 for S11<-10 dB from 5.32 to 5.52 GHz. A radiation pattern with broadside radiation and low back radiation has been obtained. A good measurement gain of approximately 13 dB is achieved over the bandwidth by placing CDRA feeder at the focal point of the parabolic reflector. In addition, a comprehensive parametric study has been conducted to realize the effect of slot size and position on the resonance frequency of the designed feeder. Furthermore, a parametric study of various reflector parameters has also been performed to study the effect of size, depth and focal point of the parabolic reflector on gain of the antenna. Important design factors have been identified from the parametric study of the antenna. The experimental and measured results show that the designed antenna is suitable for IEEE WLAN 802.11a wireless application. Â© Maxwell Scientific Organization, 2015.